Zhizn' pod grifom sekretno . Life Under the Label Top Secret - Krichevskii, Grigorii (NTV, 2001)
The film tells the story of the escape of two Soviet intelligence agents from the US in 1948. It was with the help of these secret agents that the first Soviet computer was built; they also tookpart in design work in Zelenograd, envisioned as a version of Silicon Valley in the suburbs of Moscow. The history of Soviet science in the 1950-60s.